Use of medication and nutritional supplements in track and field athletes - Tscholl, P.; Alonso, J. M.; Jungen, A.; Dolle,m G.; Dvorak, J. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
High use of medication and nutritional supplements has been reported in several sports. Athletes participating in team sport events seem to have a higher use of painkilling agents than in individual sport events, whereas higher use of nutritional supplements and beta-2-agonists has been reported in individual sport athletes. Several authors have raised the question whether prescription practice corresponds to medical indication. Detailed analysis in track and field athletes is scarce, especially concerning different age groups and disciplines. This study focuses on the use of prescribed medication and nutritional supplements of track and field athletes depending on their sports discipline with special regard to gender, age, and geographic origin. Methods: 3`887 doping control forms were analysed undertaken during twelve IAAF World Championships (2003 - 2008) and one entire out-of-competitions season (2007) in track and field athletes. Results: 6`523 nutritional supplements (1.7 per athlete) and 3`237 medications (0.8) were reported by the athlete. Non-steroidal antiinflammatory drugs (NSAIDs; 0.27, n=884), respiratory drugs (0.21, n=682), and alternative analgesics (0.13, n=423) were used most frequently. Medication use increased with age (0.33 to 0.64 per athlete) and decreased with increasing duration of the event (from sprints to endurance events) (0.11 to 0.60). African and Asian athletes reported using significantly fewer supplements (0.85 versus 1.93) and medications (0.41 versus 0.96) than other athletes. Compared with middle distance and long distance runners, athletes in power and sprint disciplines reported using more NSAIDs, creatine and amino-acids, and fewer antimicrobial agents. The final ranking in the championships was unrelated to the quantity of reported medications or supplements taken. Conclusions: The use of NSAIDs in athletics is less than that reported for team-sport events. However, nutritional supplements are used more than twice as often as they are in international football competition. Significant differences were found between the different disciplines regardless of geographic origin. Nevertheless, African and Asian athletes seem to receive lesser pharmaceutical support by their team physicians than other athletes. Whether some of the athletes are over-medicated or others under-supplied due to lower financial resources needs special regard in the future. Both over-medication and under-medication may have detrimental effects not only for the athletes` health status but also for their sports performance. It therefore is absolutely essential that an evidence-based approach to the prescribing of medication and nutritional supplements is adopted, to protect the athlete`s health and prevent them from testing positive in doping controls.